암호화 및 유효성 검사를 통한 함정 전투체계의 설치 보안 향상 연구 - 이병완(Byeong-Wan Lee) (한국컴퓨터정보학회논문지, 2024)
본 논문에서는 함정 전투체계 소프트웨어 설치 시 발생 가능한 데이터 이상을 확인하는 설치 방안을제안한다. 최근 저궤도 위성 통신과 같은 무선 통신을 이용한 정보교환 방법이 대중화되며, 함정 전투체계에서도 무선망을 이용한 여러 활용 방안이 논의되고 있다. 활용 방안 중 하나로서 무선망 통신을이용한 설치를 함정 전투체계에 적용함으로써 실시간으로 전투체계 성능을 향상시킬 수 있는 방법이가능해질 것으로 기대한다. 하지만 무선망의 경우 유선망보다 상대적으로 보안상 취약하므로 더 많은보안 대책이 강구된다. 본 논문에서는 암호화 방식을 통해 다수의 노드에 파일을 전송하고 파일 설치이후 유효성 검사를 수행함으로써, 전송 도중 위/변조 여부를 판단하여 정상적으로 설치됨을 확인한다. 제안한 방법의 함정 전투체계 적용 가능성을 보이기 위하여 전송 성능 및 보안성, 안정성 등을 평가하였으며, 이를 바탕으로 함정 전투체계에 적용하기 충분한 수준의 결과물을 도출하였다. In this paper, we propose an installation approach for Naval Combat Management System(CMS) software that identifies potential data anomalies during installation. With the popularization of wireless communication methods, such as Low Earth Orbit(LEO) satellite communications, various utilization methods using wireless networks are being discussed in CMS. One of these methods includes the use of wireless network communications for installation, which is expected to enhance the real-time performance of the CMS. However, wireless networks are relatively more vulnerable to security threats compared to wired networks, necessitating additional security measures. This paper presents a method where files are transmitted to multiple nodes using encryption, and after the installation of the files, a validity check is performed to determine if there has been any tampering or alteration during transmission, ensuring proper installation. The feasibility of applying the proposed method to Naval Combat Systems is demonstrated by evaluating transmission performance, security, and stability, and based on these evaluations, results sufficient for application to CMS have been derived. KCI Citation Count: 0